ECOLOGICALLY ACCEPTABLE LUBRICANTS - Dugić, M.; Dugić, P.; Macura, R. (Journal of Engineering & Processing Management, 2009)
Increase of ecological awareness affected the realization of more strict laws concerning the environment, which are being imposed in many countries. It also affected lubricant area and tendency for decreased pollution that lubricants can induce if they are uncontrollably spread around. Earlier it was believed that biodegradability is the most important criteria for evaluating the ecologically acceptable lubricants. Many studies had given the results of testing the affect that lubricants have on flora and fauna in water, their accumulation potential and human health. European Union commission had presented in 2005. the document under number 2005/360/EC that applies on lubricants that can carry the so-called Eco-label. It defines seven basic criteria that lubricants must fulfill. Manufacturers of components for lubricant production and lubricants itself had gotten newmissions. In this paper are shown the results of lubricant testing that completely satisfy the given criteria. They apply on toxicity for flora and fauna in water, bio accumulation potential and harmful health impact potential. Special demand is applied on using feedstock that are not only biodegradable, but are produced from renewable sources, and thus fulfill technical lubricant performances.